Evaluation of a Pediatric Community-Acquired Pneumonia Antimicrobial Stewardship Intervention at an Academic Medical Center - Lauren Puzz; Emily A. Plauche; David A. Cretella; Virginia A. Harrison; Mary Joyce B. Wingler (MDPI AG, 2023)
(1) Background: Pneumonia is the leading diagnosis associated with antibiotic use in hospitalized children. The Infectious Diseases Society of America published pediatric community-acquired pneumonia (CAP) guidelines in 2011, but adherence to recommendations varies across institutions. The purpose of this study was to evaluate the impact of an antimicrobial stewardship intervention on antibiotic prescribing in pediatric patients admitted to an academic medical center. (2) Methods: This single-center pre/post-intervention evaluation included children admitted for CAP during three time periods (pre-intervention and post-intervention groups 1 and 2). The primary outcomes were changes in inpatient antibiotic selection and duration following the interventions. Secondary outcomes included discharge antibiotic regimens, length of stay, and 30-day readmission rates. (3) Results: A total of 540 patients were included in this study. Most patients were under five years of age (69%). Antibiotic selection significantly improved, with prescriptions for ceftriaxone decreasing (p < 0.001) and ampicillin increasing (p < 0.001) following the interventions. Antibiotic duration decreased from a median of ten days in the pre-intervention group and post-intervention group 1 to eight days in post-intervention group 2. (4) Conclusions: Our antibiotic stewardship intervention directed at pediatric CAP treatment resulted in improved antibiotic prescriptions and provides data that can be used to further educate providers at our institution.